Strict relationship between phenotypic and plasmid-associated genotypic of multidrug-resistant Escherichia coli isolated from Taihe Black-Boned Silky Fowl farms - Li Zhang; Mengjun Ye; Yifan Dong; Lijuan Yuan; Jianjun Xiang; Xiren Yu; Qiegen Liao; Qiushuang Ai; Suyan Qiu; Dawen Zhang (Poultry Science)
Taihe Black-Boned Silky Fowl (TBSF) is a unique breed in China, characterized by a high concentration of melanin deposited throughout its body. Compared to broiler chickens, many antibiotics exhibit significantly longer withdrawal periods in TBSF. Given that antibiotic exposure is widely recognized as the primary selective pressure driving the persistence and dissemination of antibiotic resistance genes (ARGs) across diverse environments, it is crucial to investigate the occurrence and prevalence of ARGs within TBSF farming systems. In this study, 34 Escherichia coli strains isolated from 22 TBSF farms were subjected to phenotypic and genotypic analyses. The isolates were tested for susceptibility to 28 antimicrobial drugs representing nine antibiotic classes to determine their antimicrobial resistance phenotypes. Draft genome sequences of these E. coli strains were obtained, and the ARGs carried by mobile genetic elements, particularly plasmids, were analyzed for their association with susceptibility phenotype. The genetic context of key ARGs in these E. coli isolates was further characterized. Network analysis was employed to investigate the correlations between ARGs, phenotypes, and drug residues. The results demonstrated that high rates of antimicrobial resistance were observed, with 100 % and 29.4 % of isolates exhibiting resistance to four or more and eight or more antibiotic classes, respectively. According to whole-genome sequencing, a total of 143 ARGs were identified. The antimicrobial resistance phenotypes were consistently correlated with the presence of corresponding ARGs in the 34 E. coli genomes. 100 % of the β-lactams antibiotics resistant mechanism could be attributed to the presence of the resistance gene blaTEM and/or blaOXA-10. Similarly, resistance to tetracyclines, chloramphenicols, aminoglycosides, and fluoroquinolones was fully explained by the presence of tetR and/or tetA, floR and/or cmlA, ant(3’’)-IIa, aph(3’’)-Ib, aph(6)-Id, aac(3)-IId, and aadA, and qnrS and/or mutant gyrA/parC/mdtH. The majority of these key ARGs were found to be plasmid-associated. This study verified and highlighted the prevalent horizontal gene transfer of ARGs in TBSF farms. Factors such as hygiene status, biosecurity measures, and other environmental conditions might play a more significant role than antimicrobial usage in facilitating the horizontal gene transfer of ARGs in TBSF farms. Appropriate measures should be taken to control the transmission and dissemination of these mobile genetic elements associated ARGs and prevent their entry into the human clinical environment from TBSF breeding environment.